2019
DOI: 10.1096/fj.201801862r
|View full text |Cite
|
Sign up to set email alerts
|

Moderate exercise in mice improves cancer plus chemotherapy‐induced muscle wasting and mitochondrial alterations

Abstract: Cancer cachexia is a multifactorial syndrome characterized by anorexia, body wasting, and muscle and adipose tissue loss, impairing patient's tolerance to anticancer treatments and survival. The aim of the present study was to compare the effects induced in mice by tumor growth alone (C26) or in combination with chemotherapy [C26 oxaliplatin and 5‐fluorouracil (oxfu)] and to evaluate the potential of moderate exercise. Oxfu administration to C26 mice exacerbated muscle wasting and triggered autophagy or mitoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
110
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 77 publications
(122 citation statements)
references
References 51 publications
12
110
0
Order By: Relevance
“…In this regard, healthy mice treated with FOLFOX or FOLFIRI (the combination of 5-fluorouracil and leucovorin with either oxaliplatin or irinotecan, respectively) present with reduced mitochondrial mass and oxidative capacity in the skeletal muscle [20] . Similar results have been reported in C26-bearing mice treated with chemotherapy (oxaliplatin and 5-fluorouracil) [21] , showing that anti-cancer treatment significantly increased the lifespan of C26-bearing mice but exacerbate muscle wasting as compared to untreated C26 hosts [21] . Such wasting effect has been associated with reduced peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) and cytochrome c expression and with increased markers of mitophagy, together with impaired oxidative capacity and ATP levels [21] .…”
Section: Introductionsupporting
confidence: 83%
See 3 more Smart Citations
“…In this regard, healthy mice treated with FOLFOX or FOLFIRI (the combination of 5-fluorouracil and leucovorin with either oxaliplatin or irinotecan, respectively) present with reduced mitochondrial mass and oxidative capacity in the skeletal muscle [20] . Similar results have been reported in C26-bearing mice treated with chemotherapy (oxaliplatin and 5-fluorouracil) [21] , showing that anti-cancer treatment significantly increased the lifespan of C26-bearing mice but exacerbate muscle wasting as compared to untreated C26 hosts [21] . Such wasting effect has been associated with reduced peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) and cytochrome c expression and with increased markers of mitophagy, together with impaired oxidative capacity and ATP levels [21] .…”
Section: Introductionsupporting
confidence: 83%
“…Similar results have been reported in C26-bearing mice treated with chemotherapy (oxaliplatin and 5-fluorouracil) [21] , showing that anti-cancer treatment significantly increased the lifespan of C26-bearing mice but exacerbate muscle wasting as compared to untreated C26 hosts [21] . Such wasting effect has been associated with reduced peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) and cytochrome c expression and with increased markers of mitophagy, together with impaired oxidative capacity and ATP levels [21] . Using a proteomic approach, alterations of the tricarboxylic acid (TCA) cycle and impaired expression of markers of mitochondrial fusion, fission and biogenesis have been reported in both untreated and chemotherapy-treated C26-bearing mice [22] .…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…The administration of IL4 to the C26 hosts resulted in increased tumour mass (Supporting Information, ) that however does not necessarily reflect an increased number of tumour cells. Indeed, the H&E staining revealed that more than 30% of tumour area in the IL4‐treated C26‐bearing mice (sacrificed at Day 31 after C26 cell injection) was necrotic (eosin positive) probably surrounded by small inflammatory cell infiltrate, a pattern that could not be observed in tumours isolated from C26 hosts (Day 13 after C26 implantation; Figure A and B) . A possible limitation of these results is that the histological analysis compares Day 13 C26 with Day 31 C26 + IL4 tumours.…”
Section: Resultsmentioning
confidence: 91%